Health technology assessment in evolution – focal therapy in localised prostate cancer. Issue 11 (November 2014) - Valerio, Massimo; Emberton, Mark; Barret, Eric; Eberli, Daniel; Eggener, Scott E; Ehdaie, Behfar; Jichlinski, Patrice; Ward, John F; Ahmed, Hashim U
<x xml:space="preserve">Abstract</x> Focal therapy in prostate cancer aims to treat only the part of the gland harboring clinically significant disease while preserving the rest of the tissue. This approach may substantially reduce treatment-related toxicity without compromising disease control outcomes. Short- to medium-term functional and oncological results in prospective interventional studies are promising, but comparative effectiveness research against standard of care is required to incorporate focal therapy among standard options. In this review, we discuss the actual stage of assessment and results of sources of energy commonly used to deliver focal therapy. We also provide our viewpoint on how the field will evolve in the near future.